Dynamical description of fusion-quasifission of heavy nuclei as open quantum system - Pavlii, K.V. (Вопросы атомной науки и техники, 2013)
The description of open quantum dissipative systems was analyzed on the basis of equations for the density matrix and the nonstationary Schrodinger equation with linear and nonlinear (non-Hermitian) Hamiltonians. Questions of capture, the first stage of the fusion reaction, and the nucleon transmission of interacting nuclei were considered. The quantum-dynamical description of fusion-quasifission of nuclei was proposed as open quantum system based on the calculations for emission of nucleons from the dinuclear system (DNS) and the transmission of nucleons at allowed [±n, ±p] and [±n, ±p ± (n + p)] transitions. Проведено аналiз опису вiдкритих квантових дисипативних систем на основi рiвнянь для матрицi густини i нестацiонарного рiвняння Шредiнгера з лiнiйними i нелiнiйними (неермiтовими) гамiльтонiанами. Розглянуто питання захоплення, першої стадiї реакцiї злиття, та передач нуклонiв взаємодiючих ядер. На пiдставi проведених розрахункiв pемiсiї нуклонiв з подвiйної ядерної системи (ПЯС) та передач нуклонiв при дозволених [±n, ±p] та [±n, ±p ± (n+p)] переходах, запропановано квантово-динамiчний опис злиття-квазiдiлення ядер, як вiдкритої квантової системи. Проведен анализ описания открытых квантовых диссипативных систем на основе уравнений для матрицы плотности и нестационарного уравнения Шредингера с линейными и нелинейными (неэрмитовыми) гамильтонианами. Рассмотрены вопросы захвата, первой стадии реакции слияния, и передач нуклонов взаимодействующих ядер. На основании проведенных расчетов по эмиссии нуклонов из двойной ядерной системы (ДЯС) и передач нуклонов при разрешенных [±n, ±p] и [±n, ±p ± (n+p)] переходах, предложено квантово-динамическое описание слияния-квазиделения ядер, как открытой квантовой системы.